THE ASSESSMENT OF THE LEVEL OF SATISFACTION AMONGST THE USERS OF AUTOMATED TELLER MACHINES IN AWKA METROPOLIS (Journal of Contemporary Issues in Accounting, 2022)
This study assessed the level of satisfaction among ATM users in Awka Metropolis. The examined aspects of satisfaction efficiency and ease of use all viewed from the perspective of the customers. The Survey Research Design was adopted for the study. The study used a sample of 100 bank customers in Awka South LGA. The study used Primary data source through the use research questionnaire to obtain data from the respondents. The data obtained from the respondents were analyzed using descriptive methods such as means and percentages. The findings revealed that bank customers agreed that ATMs in Awka were easy to use and efficient. The researcher recommended among other things that commercial banks should develop a working system that ensures that there are always cash in the ATM machine.
Keywords: Assessment; Satisfaction; efficiency; customer’s perception; ATM